Accurate identification of Helicoverpa armigera–Helicoverpa zea hybrids using genome admixture analysis: implications for genomic surveillance - Trujillo, Dario; Mastrangelo, Thiago; Estevez de Jensen, Consuelo; Verle Rodrigues, Jose Carlos; Lawrie, Roger; Massey, Steven E. (Frontiers in Insect Science, 2024)
Helicoverpa armigera, the cotton bollworm moth, is one of the world’s most important crop pests, and is spreading throughout the New World from its original range in the Old World. In Brazil, invasive H. armigera has been reported to hybridize with local populations of Helicoverpa zea. The correct identification of H. armigera-H. zea hybrids is important in understanding the origin, spread and future outlook for New World regions that are affected by outbreaks, given that hybridization can potentially facilitate H. zea pesticide resistance and host plant range via introgression of H. armigera genes. Here, we present a genome admixture analysis of high quality genome sequences generated from two H. armigera-H. zea F1 hybrids generated in two different labs. Our admixture pipeline predicts 48.8 % and 48.9 % H. armigera for the two F1 hybrids, confirming its accuracy. Genome sequences from five H. zea and one H. armigera that were generated as part of the study show no evidence of hybridization. Interestingly, we show that four H. zea genomes generated from a previous study are predicted to possess a proportion of H. armigera genetic material. Using unsupervised clustering to identify non-hybridized H. armigera and H. zea genomes, 8511 ancestry informative markers (AIMs) were identified. Their relative frequencies are consistent with a minor H. armigera component in the four genomes, however its origin remains to be established. We show that the size and quality of genomic reference datasets are critical for accurate hybridization prediction. Consequently, we discuss potential pitfalls in genome admixture analysis of H. armigera-H. zea hybrids, and suggest measures that will improve such analyses.